Perbedaan Karakteristik Kunjungan ke Ruang Terbuka Hijau di Masa Pandemi Covid-19: Studi Kasus Taman Kota di Kota Bekasi: Differences in the Characteristics of Green Open Space Visits during The Covid-19 Pandemic: A Case Study of City Parks in Bekasi City - Annamaria Heni Ayuningtyas; Rulli Pratiwi Setiawan (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
Green open space is one of the most needed spaces in a city, especially during the Covid-19 pandemic. However, the number of green open spaces in many cities is insufficient. Another problem is the increasing population growth which has an impact on the need for built-up land. The emergence of the Covid-19 pandemic has raised people’s awareness on the need for green open spaces. The presence of green open spaces in the form of city parks is widely used by the community for various activities during the Covid-19 pandemic. Therefore, it is necessary to understand the differences in the use of parks and park visits, both before and during the Covid-19 pandemic. This study aims to analyze the differences between the characteristics of park visits before and during the Covid-19 pandemic and the socioeconomic characteristics of the visitors. Analytical methods used in this study include a cross-tabulation analysis, Chi-square test, and Cramer’s V test to determine whether there are relationships and to identify the strengths of the existing relationship between the characteristics of park visits and visitors before and during the Covid-19 pandemic. Data on the characteristics of park visits and visitors were obtained through an online survey. A number of 141 valid responses were used for further analysis. Results of this study indicated that there are differences in park visits related to the characteristics of visitors before and during the Covid-19 pandemic. The differences in the characteristics of park visits are found in the frequency of visits, duration of visits, and habitual companion.